KARAKTERISTIK TEPUNG KOMPOSIT YANG DISUPLEMENTASI RUMPUT LAUT SEBAGAI BAHAN BAKU PRODUK KULINER - . Kartiwan; Zulianatul Hidayah; Bachtaruddin Badewi (Partner, 2009)
Composite Flour Characteristics At Suplementasi Sea Grass Upon Which Standard Kuliner Product. The experiment was conducted at Food Technology Laboratory Politani Negeri Kupang lasted on April  to November 2008. The objectiveresearch  to  produced good  quality  composite flours  to    prepare  data  base  for produce excellent quality culinary product. The experiment used RCBD and 3 replications. The treatments were six  flour formulas base on wheat and indigenous flour  (K1 up to K6 added by  indigenous flours 15%, 30%, 45%, 60%, 75% and 90% respectively). The indigenous flours were combination from waxy corn, sorghum,sweet potatoes, and seaweed. The variables observed were water absorption, gelatination, liquid viscosity, pulp  thickness,   expansion of  dough. Data    were analised using Anova and DMRT.The gelatination temperature and water absorption were increased at composite flours with  high indigenous flour contents. Viscocity and the dough expansion of composite flour decreased with high indigenous  flour contents. The pulp thickness of composite flours as same as character with liquid viscosity.Keywords: composite flours, supplementation, seaweed, culinar